Carrier transport of carbon nanotube embedded organic semiconductor composite. (June 2017) - Song, Young Seok; Bok, Moonjeong; Lim, Eunju
Graphical abstract: Highlights: The carrier transport of an organic semiconductor composite was investigated. The TIPS/CNT composites offered enhanced DC electrical conductivity. The carrier trapping of the composite increased by embedding CNTs. Abstract: This study exploits the carrier transport of an organic semiconductor composite incorporated with carbon nanomaterials. Carbon nanotubes (CNTs) were employed as a conductive inorganic nanofiller, and 6, 13-Bis(triisopropylsilylethynyl)pentacene (TIPS) was applied as an organic semiconducting material to evaluate gate-voltage (VGS ) of field effect transistors (FETs). The direct current (DC) electrical conductivity was controlled by adding the CNTs into the composite, and the resulting characteristics of terminals, sources and drain-source voltage (VDS ) of transistors were evaluated. Our experimental results revealed that the TIPS/CNT composites offered enhanced DC electrical conductivity, e.g., above 0.195 S/m. These findings demonstrated that the carrier trapping of the organic semiconductor significantly increased by embedding CNTs. The TIPS and TIPS/CNT OFETs were analyzed using the Maxwell-Wagner model to understand the carrier mechanisms in the CNTs embedded OFET device.